Pendidik Transformatif: antara Disrupsi dan Pandemi Covid-19 - Mohammad Ulil Abshor (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2021)
The era of disruption presupposes that if you do not continue to innovate, then backwardness is a must. Because the rapid and even surprising development of technology today requires us to immediately make adjustments to it. Especially for educators, besides being required to master and adapt to developments and changes, they are also expected not to lose the educator's soul. This paper wants to discuss the challenges for educators in the era of disruption and also, about how educators respond to these developments. This research uses the descriptive analysis method by collecting data related to the research. The results of this study are that there are several challenges that must be faced by educators, including mastering technology, maintaining the educator's soul and trying to cross-breed the two (hybridization) on the basis of subjective-critical reasoning. These three things are urgent offers at this time, because considering the developments and changes in the era that are so fast and surprising, simultaneously there is growing concerned about the neglect of the purpose of education itself, namely, humanizing humans.